POTRET GAYA KEPUTUSAN PEMBELIAN MASYARAKAT KOTA PADANG DALAM MEMBELI MOBIL SEGMEN LOW MPV - Dharma, Surya; Yuliviona, Reni; Utari, Riesa Diana (LLDIKTI Wilayah X, 2016)
The main aim of this research was to identify Low MPV consumersâ decision making style in Padang by using Consumer Styles Inventory (CSI). Â According to the CSI, one can capture what decision-making styles low-MPV car use.Â Â Furthermore,Â this research also discusses the type of Low-MPV differences among consumers.Â Confirmatory factor analysis (CFA) was used to confirm the decision-making styles and Chi-Square Test to distinguish the differences between Low MPV type.Â Â Â The results shows that there are differences in purchasing decisions making style between Toyota Avanza, Suzuki Ertiga, Honda Mobilio and Daihatsu Xenia.Â Toyota Avanza consumers identified as perfectionist style and Suzuki Ertiga consumers as price conscious style while making a decission to buyThe main aim of this research was to identify Low MPV consumersâ decision making style in Padang by using Consumer Styles Inventory (CSI). Â According to the CSI, one can capture what decision-making styles low-MPV car use.Â Â Furthermore,Â this research also discusses the type of Low-MPV differences among consumers.Â Confirmatory factor analysis (CFA) was used to confirm the decision-making styles and Chi-Square Test to distinguish the differences between Low MPV type.Â Â Â The results shows that there are differences in purchasing decisions making style between Toyota Avanza, Suzuki Ertiga, Honda Mobilio and Daihatsu Xenia.Â Toyota Avanza consumers identified as perfectionist style and Suzuki Ertiga consumers as price conscious style while making a decission to buy